PEMETAAN DISTRIBUSI KEJADIAN DAN FAKTOR RISIKO STUNTING DI KABUPATEN BANGLI TAHUN 2019 DENGAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Putra, Putu Aris Budiyasa; Suariyani, Ni Luh Putu (ARCHIVE OF COMMUNITY HEALTH; Vol 8 No 1 (2021): April 2021DO - 10.24843/ACH.2021.v08.i01.p06, 2021)
ABSTRACT Based on 2018 Riskesdas, Bangli Regency take first place as a district with the highest proportion of stunting in the Province of Bali, around 43.2%. The occurrence of stunting is influenced by multiple factors including, geographical, and even demographic of the areas. descript stunting using GIS (Geographic Information System) is useful to find out the pattern of the spread of stunting and the relationship of stunting events to the risk factors of stunting in an area. This study was used a descriptive cross-sectional design. It descript the distribution of stunting number and risk factors used a map processing application in the GIS process. The results of the study illustrate stunting cases spread across all over the districts with the highest cases in Susut District and the lowest in Bangli District. In some areas with high cases of stunting, they are far from puskesmas services. The Bangli Regency is dominated by rural areas with a large distribution of cases in rural areas. Stunting cases are often found in the plains and mountains. Some areas that have low coverage of Healthy Latrine (JSP) have high number of stunting . The pattern of the occurrence of stunting cases in Bangli Regency in 2019 along with the risk factors can be illustrated through a map of the distribution of stunting cases and layering of each risk factor. It is recommended to be able to consider stunting distribution maps in making stunting policy in Bangli Regency. Keywords: Sunting, Maping, GIS